2021
DOI: 10.1021/acscatal.0c04171
|View full text |Cite
|
Sign up to set email alerts
|

O-/N-/S-Specificity in Glycosyltransferase Catalysis: From Mechanistic Understanding to Engineering

Abstract: Glycosyltransferases (GTs) catalyze the formation of glycosidic bonds in carbohydrates and glycoconjugates, with various outcomes depending not only on the acceptor molecules they bind but also on the type of glycosidic bond they form (C−O, C−N, C−S, or C−C). Here we show that the glucosyltransferase UGT1 from the indigo plant Polygonum tinctorium catalyzes either N-, O-, or S-glycosylation with similar rates. We solve the structure of the enzyme in complex with its donor and acceptor substrates and elucidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 40 publications
3
83
0
Order By: Relevance
“…GTs catalyze stereoselective glycosylations with either retention or inversion of the anomeric configuration. Experimental and computational studies agree with an S N 2‐like mechanism for inverting GTs, usually involving the deprotonation of the nucleophile by a catalytic base (Figure 3a) [45,46] . In contrast to inverting GTs, the reaction mechanism for retaining GTs is not fully understood.…”
Section: Selective Alkylation With Anomeric Carbon Atomsmentioning
confidence: 84%
“…GTs catalyze stereoselective glycosylations with either retention or inversion of the anomeric configuration. Experimental and computational studies agree with an S N 2‐like mechanism for inverting GTs, usually involving the deprotonation of the nucleophile by a catalytic base (Figure 3a) [45,46] . In contrast to inverting GTs, the reaction mechanism for retaining GTs is not fully understood.…”
Section: Selective Alkylation With Anomeric Carbon Atomsmentioning
confidence: 84%
“…For this purpose, however, the analytics for characterization of the free and immobilized biocatalysts were not based on the eventual substrate indoxyl but on the well-accepted model compound 3,4-dichlorophenol (DCP). 18 This measure was taken (i) to improve intrinsic analytical precision by removing errors caused by analyte instabilities, (ii) to use a commercially available substrate of high purity, eliminating needs for upstream in situ indoxyl generation and therefore (iii) facilitating a more economic and ecologic screening process by avoiding otherwise necessary material and time-consuming steps. DCP was selected as model compound since it is a readily available substrate of comparable molecular weight, water solubility, pKa and hydrophobicity (logP) as given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…PtUGT1. 18 Thus, for further characterization of free enzyme, we as well opted for the HEPES buffer at this pH. However, considering the potential technical relevance of biocatalytic indican and the associated economic requirements, there is limited utility in the evaluation of conditions which are too far from economic feasibility.…”
Section: Resultsmentioning
confidence: 99%
“…Typically an aspartate, glutamate, or a coupled His/Glu plays the role of such a catalytic base ( Figure 2 A). 3 , 18 Interestingly, site-directed mutagenesis studies on Ce POFUT1 and Drosophila melanogaster POFUT1 showed that two active site residues, an arginine and an asparagine, are essential for enzyme activity. 15 Both residues are conserved among species (see Supporting Information, SI, Figures S1 and S2 ).…”
mentioning
confidence: 99%
“…Inverting GTs typically involve an aspartate, a glutamate, or even a histidine as a catalytic base. 18 However, Asn is known to act as an acid/base residue in enzymes that catalyze light-activated processes. 34 Amide–imide tautomerization has also been proposed, although not confirmed, for glycoprocessing enzymes such as families 45 and 85 glycosidases.…”
mentioning
confidence: 99%